Analisis Strategi Pengembangan Usaha Kreatif Berbasis Wickercane Dengan Metode Analisis SWOT - Fauziah, Rahma Misbah; Arif, Muhammad (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
This research aims to systematically analyze the various factors that influence the sustainability of the rattan (wickercane) wall decoration craft business. Indonesia, as a country with the largest rattan reserves in the world, has strategic potential in developing a rattan-based creative economy that can drive national economic growth and open up jobs. Around 80% of the world's raw rattan supply comes from Indonesia, with a rattan forest area of ​​around 10 million hectares and an annual production of 600 thousand tons. This study uses a SWOT analysis approach that produces four strategies: SO by maximizing the strengths of rattan, batik, and design innovation; WO through strengthening branding; ST through increasing competitiveness through storytelling; and WT with a market research approach and distribution collaboration. These strategies are expected to be able to optimize potential, reduce weaknesses, anticipate challenges, and open up future opportunities. This study can be a strategic foothold for business actors and stakeholders in strengthening the rattan creative industry in Indonesia.